علم اسباب ِورودِ حدیث؛ تعارف، آغاز وارتقاء (علامہ ابن حمزہ دمشقی کی کتاب’البیان‘ کا خصوصی مطالعہ) : Knowledge of the Origins of Hadith: Introduction, Beginnings and Development (A special study of Allama Ibn Hamza Damaschi’s book, Al Bayan) - Sajid, Zia Rasool; Shabana, Dr. Razia (Al-Amīr Research Journal for Islamic Studies, 2024)
The knowledge of the hadiths of the Messenger of Allah (peace and blessings of Allah be upon him) is great in every respect. It is a revelation like the Qur’an. This book is a brief interpretation of Allah. The Holy Qur’an contains general instructions. But the description of these instructions is impossible and impossible without knowing the knowledge of Hadith. Following the departure of the Messenger of Allah (peace and blessings of Allah be upon him) is possible only through the Sunnah. The complete and correct knowledge of the Sunnah depends on another thing besides the text of the hadith, which is called the causes of the hadith. From this knowledge, it is known which hadith. When, where and why has it arrived? What was the atmosphere like when the Prophet (PBUH) ordered something or forbade something? In order to understand the hadith correctly, knowledge of the causes of the hadith is required. Knowledge of this knowledge is essential for a Muslim in general and for a Mujthid in particular. Faith and love require that we get to know the character, attributes and commandments of the Prophet of whom we are the ummah. So that faith and love reach the level of perfection. The purpose of this article is to describe the introduction of knowledge of hadith and hadith for understanding hadith. Key Words: Hadith, Sunnah, Revelation, Causes of Hadith, Ibn e Hamza Damishqi, Kitāb ul-Biyān.